A coupled 1D film hydrodynamics and core gas flow model for air-oil flows in aero-engine bearing chambers - Kakimpa, Bruce; Morvan, Herve; Hibberd, Stephen (2017)
A robust 1D film hydrodynamic model has been sequentially coupled with a 1D core gas model and used to predict the instantaneous mean core gas speed, film interface shear stress and liquid film distribution within an idealised bearing chamber. This novel approach to aero-engine bearing chamber simulation provides a predictive tool that can be used for the fast and reliable exploration of a set of bearing chamber design and operating conditions characterised by the: chamber dimensions, air/oil fluid properties, shaft speed, sealing air flows, oil feed rates and sump scavenge ratios. A preliminary validation of the model against available bearing chamber flow measurements from literature shows good agreement. The model represents a significant step change in predictive capabilities for aero-engine oil system flows compared to previous semi-empirical models. The bearing chamber is idealised as a one-dimensional (2D) domain with a predominantly azimuthal flow in both the rotational oil film and core gas such that axial components may be ignored. A 1D system of depth-averaged film hydrodynamics equations is used to predict oil film thickness and mean speed distributions in the azimuthal direction under the influence of interface shear, gravity, pressure gradient and surface tension forces. The driving shear stress in the film model is obtained from the 1D core-gas model based on an azimuthal gas momentum conservation equation which is coupled to the film model through the interface shear stress and film interface velocity.